Types of expertise in political decision-making in education: Contributions from a theoretical and conceptual discussion - Carina Coelho; Manuela Terrasêca; José Alberto Correia (Arizona State University, 2016)
In this article we present some reflections from a conceptual analysis and discussion that are part of a wider research intending to understand and questioning current ways of expertise in educational policy-making, namely, concerning to the characteristics of the expert actors and the kind of knowledge recognized as valid to legitimize political decisions. Starting from a contextualization of the research interests in the recent (last decades) changes on modes of governance and policy decision-making, we synthesize and try to put in discussion the perspective of some authors, in an approach to the concepts of expert and expertise that take as particular reference the articulations established between these and other concepts, professional fields and nearby spheres of action. Some considerations that have resulted from this analysis indicate an interpretative variability with such amplitude that allows the inclusion of opposite concepts for expert, especially if we consider knowledge formalization level and knowledge specialization level. We also provide some clues about the pertinence of analyzing political decision-making processes through an approach of the expert as a collective figure.